Pengaruh Sales Growth dan Keahlian Keuangan Komite Audit terhadap FinancialDistress.(Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Otomotif dan Komponen yang Terdaftar di Bursa Efek IndonesiaPeriode 2012-2016) - Nurhayati Nurhayati; Kania Nurcholisah; Topan Aprian (Kajian Akuntansi, 2019)
Abstract. This study aims to determine the effect of sales growth and financial expertise of audit committee to financial distress. The research method used is descriptive research method with quantitative approach. Analyzer used in this research is multiple regression analysis by using sample of research as many as 9 manufacturing companies of the automotive and component sub-sector listed on The Indonesia Stock Exchange in 2012-2016. Hypothesis testing is done by multiple linear regression method using  SPSS version 17. The result showed that the sales growth variable has no significant negative effect to financial distress, and  financial expertise of audit committee has negative and significant effect to financial distress. The result of this study can be recommendation for investor to be able to analyse the company’s financial statements related to the decision to invest. Recommendation for the next researchers to be able to research all of manufacturing companies listed on Indonesia Stock Exchange and used other indicator of financial ratios contained in balance sheet, income statements, and cash flow statements.Keywords: Financial Distress, Audit Committee Financial Expertise, Sales Growth.